‘Metaprevotella massiliensis’ gen. nov., sp. nov., isolated from human ileum - Ricaboni, D. (New Microbes New Infect, 2016)
We report here the main characteristics of ‘Metaprevotella massiliensis’ strain Marseille-P-3114(T) (CSURP3114) that was isolated from a human ileum sample.